NEW ELEMENTS OF TECHNOLOGY FOR THE GROWING AND PROTECTION OF TOBACCO FROM HARMFUL ORGANISMS AND ITS ECONOMIC SUBSTANTIATION (INNOVATIVE ECONOMY, 2020)
Bialkovska H.D., Pashchenko V.I. NEW ELEMENTS OF TECHNOLOGY FOR THE GROWING AND PROTECTION OF TOBACCO FROM HARMFUL ORGANISMS AND ITS ECONOMIC SUBSTANTIATIONPurpose. The aim of the article is to study the influence of ecologically safe pesticides on a height and development of plants of tobacco and realization of economic evaluation of his results.Methodology of research. Scientific methods are used in the process of the study: bibliographic (study and working of scientific works that touch technology of growing of tobacco); agronomical - for the study of norms of bringing of experimental preparations; economic method – at treatment of results of scientific researches for 2016-2018 years; method of comparative analysis – for the estimation of economic efficiency of different technologies of growing of tobacco.Findings. The new elements of technology of growing and defence of tobacco are reasonable from illnesses and wreckers and she is conducted complete economic evaluation. Recommendations are worked out with the use of growth factor Pennant and to insecticide Commander as effective preparations of increase of the productivity and quality of tobacco raw material of new variety of tobacco of the Ukrainian selection Berley 46 in the agro-climatic conditions of Prydnistrovia of Ukraine. Their application considerably promotes the level of profitability of process of growing of tobacco raw material due to the increase of firmness of plants to the unfavourable factors of environment and assists the increase of competitiveness of tobacco industry of our state in the world market.Originality. In the process of research next results that have a scientific novelty are got: the new elements of technology of growing and defence of tobacco are worked out from illnesses and wreckers with the use of new environmentally sound preparations – growth factor Pennant and to insecticide knight Commander on the tobacco areas of sort Berley 46 in the Prydnistrovia’s region of Ukraine. The indexes of economic efficiency of new elements of technology are reasonable.Practical value. An application domain is agricultural enterprises of Prydnistrovia of Ukraine of all legal forms that engage in growing of tobacco.Key words: tobacco; varieties; technology; immunity; diseases; pests; growth promoters; insecticides; cost; price; profit; profitability level; economic efficiency.
Keywords: Key words; tobacco; varieties; technology; immunity; diseases; pests; growth promoters; insecticides; cost; price; profit; profitability level; economic efficiency.